Interactive Media and Classroom Communication: The Role of Pagar Sapa in Shaping Student Engagement in Primary Education - Krisbiantoro; Tinus, Agus; Syahri, M (Mediakita, 2026)
This study aims to explore the Pagar Sapa interactive learning tool in encouraging student engagement, participation, and understanding while highlighting the critical role of teachers as educators, facilitators, and motivators at MI Muhammadiyah 3 Ngunut. A qualitative research design was employed, using classroom observations and in-depth interviews with teachers and students. Data were analyzed using thematic analysis to identify patterns related to student engagement and teachers’ roles in optimizing learning experiences through the Pagar Sapa media. Findings show that the Pagar Sapa media significantly increased student participation, motivation, and conceptual understanding in learning mathematics. Teachers effectively integrated Pagar Sapa to foster an interactive learning environment, aligning with their three primary roles. As educators, teachers provided structured and engaging explanations; as facilitators, teachers developed and adapted learning materials to meet students’ needs; and as motivators, they encouraged active participation and boosted students’ confidence through positive reinforcement. This study emphasizes the importance of equipping teachers with the skills to use interactive media effectively and to improve mathematics teaching through engaging, student-centered methodologies.